Acute microglia ablation induces neurodegeneration in the somatosensory system. Issue 1 (December 2018) - Rubino, Stephen; Mayo, Lior; Wimmer, Isabella; Siedler, Victoria; Brunner, Florian; Hametner, Simon; Madi, Asaf; Lanser, Amanda; Moreira, Thais; Donnelly, Dustin; Cox, Laura; Rezende, Rafael; et al.
Abstract Previous studies have reported that microglia depletion leads to impairment of synapse formation and these cells rapidly repopulate from CNS progenitors. However, the impact of microglia depletion and repopulation in the long-term state of the CNS environment has not been characterized. Here, we report that acute and synchronous microglia depletion and subsequent repopulation induces gray matter microgliosis, neuronal death in the somatosensory cortex and ataxia-like behavior. We find a type 1 interferon inflammatory signature in degenerating somatosensory cortex from microglia-depleted mice. Transcriptomic and mass cytometry analysis of repopulated microglia demonstrates an interferon regulatory factor 7-driven activation state. Minocycline and anti-IFNAR1 antibody treatment attenuate the CNS type 1 interferon-driven inflammation, restore microglia homeostasis and reduce ataxic behavior. Neither microglia depletion nor repopulation impact neuropathology or T-cell responses during experimental autoimmune encephalomyelitis. Together, we found that acute microglia ablation induces a type 1 interferon activation state of gray matter microglia associated with acute neurodegeneration. Previous studies have shown that depletion of microglia at early developmental stages leads to neuronal death. Here the authors use an inducible system to ablate microglia in adulthood, showing that such depletion leads to ataxia-like behavior and neuronal loss, and identifying the inflammatory components that may contribute.